Estimation of suitable extractant and critical level of B in cauliflower (Brassica oleracea var. botrytis, cv. Sabour Agrim) for the soils of Indo-Gangetic plain of Bihar, India - MANDAL, JAJATI; KUMAR, SUNIL; PADBHUSHAN, RAJEEV (The Indian Journal of Agricultural Sciences, 2019)
This study is a synthesis of information on suitable extractant, critical level of B in soil and plant using cauliflower (Brassica oleracea var. botrytis) (Variety: Sabour Agrim) as a test crop grown in Inceptisols, Entisols and Alfisols of Indo-Gangetic plain of Bihar,India. A pot experiment was conducted with soils from 15 locations and five levels of B ( 0, 0.5, 1.0, 2.0 and 3.0 mg B kg-1) and was replicated thrice. Four extractant methodologies were used for determination of B. The critical level of B in soil and plant was 0.55 and 21.15 mg kg-1 respectively. Among the four extractant methodologies, viz. hot-water-soluble (HWS), 0.02M hot-CaCl2 (HCC), 0.5 (M) KH2PO4(PDP) and 0.05 (M) HCl used in the present study. HCC proved to be the suitable extractant depending on the soil properties. Assessment of different B application rates revealed that the application of B should be between 0.4 to 3.0 mg kg-1 to avoid deficiency and toxicity symptoms and 2.0 mg kg-1 of B application emerged as the best treatment.